Rapid Results!: How 100-Day Projects Build the Capacity for Large-Scal e Change - Schaffer, Robert H.; Ashkenas, Ron (Jossey-Bass, 2005)
Rapid Results! shows how to make large-scale changes succeed  by using 100-day results-producing projects to develop this vital implementati on capability. Written by Robert H. Schaffer, Ronald N. Ashkenas, and their associates—leaders in the field of change management—Rapid Resul ts! describes an approach that has been field-tested by real organizat ions of every size and description to improve performance and speed th e pace of change. Rapid results projects produce results quickly, intr oduce new work patterns, and enable participants to learn a variety of lessons about managing change. Step by step, the book describes how t he use of rapid-cycle, or 100-day, projects   will multiply your organ ization’s power to succeed at large-scale change. Schaffer and Ashkena s specifically outline the concept behind 100-day projects and show yo u how to Set up the architecture to implement rapid results projects I mprove operational performance and also attain hard results in the sof t areas of management Build rapid results into major organizational ch ange such as reorganization, acquisition integration, and internationa l development Use rapid results to drive leadership development and cu lture change